The Influence of Health Service Quality on Patient Satisfaction: A Study at Bontonompo 2 Primary Health Center - Harma, Asmarani; Ishak, Syamsul (Sean Institute, 2025)
Service quality is a major determinant of patient satisfaction in primary health care. In Indonesia, community health centers (puskesmas) are the first point of contact for most patients, yet challenges remain in ensuring patient-centered care. This study aimed to analyze the influence of health service quality on outpatient satisfaction at Bontonompo Primary Health Center, South Sulawesi, Indonesia. A quantitative cross-sectional design was applied to 50 outpatients recruited through accidental sampling. Inclusion criteria were patients aged 12 years or older who had received outpatient services and consented to participate. Data were collected using a structured questionnaire adapted from the SERVQUAL framework, covering five service quality dimensions—tangible, reliability, responsiveness, assurance, and empathy—and patient satisfaction, all measured on a four-point Likert scale. Descriptive statistics were used to describe sociodemographic characteristics, perceived service quality, and satisfaction. Chi-square tests and simple linear regression were applied to determine associations and the predictive influence of service quality on satisfaction, with a significance level of p < 0.05. Respondents were predominantly female (72%), aged 12–77 years, and most had completed senior high school (32%). Overall satisfaction levels were high, ranging from 82% to 100%, with two items achieving complete satisfaction. Nevertheless, one service quality indicator recorded dissatisfaction among 68% of respondents. Statistical tests confirmed a significant positive relationship between service quality and patient satisfaction (β > 0, p < 0.05). Health service quality significantly influences outpatient satisfaction at Bontonompo Primary Health Center. While overall satisfaction is high, improvements are needed in responsiveness and empathy. Recommendations include enhancing staff training, reducing waiting times, and implementing routine satisfaction surveys to support continuous quality improvement.